A study on the frequency of iron deficiency and thalassaemia in blood donors at Pusat Darah Negara, Kuala Lumpur - Lim, W. C.; Hanachi, Parichehr; Abdul Karim, Faraizah; Asidin, Norhanim; Ayob, Yasmin; Duraisamy, G. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
This study was done to identify lood donors with thalassaemia and iron deficiency. A cross sectional study was carried out at Pusat Darah Negara (PDN), Kuala Lumpur in November 2003. Methods: Full blood counts were done on 242 blood donors (166 males and 76 females) Hb analysis and serum ferritin assay were done for all the samples. The first time donors were used as controls. Results: Only 20 (8.3%) donors had MCV <80 fl and MCH <26 pg. six of the 25 donors with iron deficiency had a low MCV (<80fi) and low MCH (<26 pg) but all the 8 (40%) donors with thalassaemia or HbE had a lowMCV and MCH. The mean ferritin levels were found to be lower among regular blood donors (95.3μg/L) compared to first time blood donors (116.6 μg/L) but this was not statistically significant. There were 25 donors who were iron deficient: one was a first time donor and 24 were regular donors – 12 (50%) had donated 3 times a year in the last two years. Iron deficiency was seen in 12 Malays, and 9 Chinese and 4 Indians. 13.3 % of the male2 (22 out of 166 donors) and 4% (3 of 76) of female donors were iron deficient. Thalassaemia and HbE were found in 8 donors. HbE trait was identified in 5 malay donors, one malay and 1 chiniese donor had β thalassaemia trait. Another Chinese had alpha (α) thalassaemia trait. Neirther HbE nor thalassaemia were seen in the Indian donors. Conclusion: In this study thalassaemia and HbE were seen in 33% and iron deficiency in 10.3 % of the 242 blood donors at PDN. Iron deficiency was present in 32% of the S> Ferritin done for their iron status and if their MCV and MCH are low, Hb analysis for thalassaemia or haemoglobinopathy.